1987
DOI: 10.1366/0003702874447356
|View full text |Cite
|
Sign up to set email alerts
|

Direct Supersonic Expansions of Supercritical Fluids for Analysis of Polycyclic Aromatic Hydrocarbons

Abstract: Significant line-narrowing has been observed in the laser-induced fluorescence spectra of naphthalene and perylene in direct supersonic expansions of simple supercritical carriers such as CO2, N2O, and even SF6, under conditions which minimize aerosol and cluster formation. Clusters form readily in expansions of CO2 and N2O unless nozzle temperatures exceed about 200°C. Results with more complex carriers, such as n-pentane, are much poorer. Selective detection of perylene at a limit of 2 ng (S/N = 3) in a mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…With total fluorescence detection, the limit of detection for perylene was found to be SO0 pg at a signal-to-noise ratio of three. This level represents an improvement of nearly three orders of magnitude over previously reported detection limits (35) and a fourfold improvement over our earlier direct-expansion results (14). The response was linear at least up to 100 ng, which was the largest amount injected.…”
Section: Smith Et Al (3 L) and Us (25)supporting
confidence: 54%
See 1 more Smart Citation
“…With total fluorescence detection, the limit of detection for perylene was found to be SO0 pg at a signal-to-noise ratio of three. This level represents an improvement of nearly three orders of magnitude over previously reported detection limits (35) and a fourfold improvement over our earlier direct-expansion results (14). The response was linear at least up to 100 ng, which was the largest amount injected.…”
Section: Smith Et Al (3 L) and Us (25)supporting
confidence: 54%
“…The analytical utility of SJS was first demonstrated by Hayes and Small and co-workers (10,ll) and Amirav et al (12). We and oiliers later showed that S3 spectra of large, nonvolatile compounds could be obtained by using supercntical fluid carriers ( I [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Experiments can be carried out either as a direct expansion of the fluid (14,15) or by introducing the effluent from the column into a secondary, noble gas expansion (7,16).…”
Section: Introductionmentioning
confidence: 99%
“…Primary restriction of the supercritical flow must be abrupt in order to avoid aggregation of solute molecules, but because the secondary expansion with makeup gas produces the supersonic cooling effect, the restrictor need not meet all of the requirements of a supersonic jet nozzle. Both porous frit plugs and abruptly tapered capillaries work well as primary restrictors, even though neither performs adequately as a direct expansion nozzle (5). The porous-frit restrictors are more convenient to use and less prone to cause solute aggregation than are tapered capillaries ( 5 ) , but we note that after extensive use, they eventually produce split peaks and band broadening.…”
Section: Resultsmentioning
confidence: 98%
“…Although supercritical fluids appear to be attractive media for introducing nonvolatile samples into the jet, it is important to appreciate certain aspects of the behavior of the expanding fluid in the design of SFC-SJS experiments. Work on direct expansions has been invaluable to us in this regard (1,5 ). Primary restriction of the supercritical flow must be abrupt in order to avoid aggregation of solute molecules, but because the secondary expansion with makeup gas produces the supersonic cooling effect, the restrictor need not meet all of the requirements of a supersonic jet nozzle.…”
Section: Resultsmentioning
confidence: 99%
“…These include synchronous fluorescence spectroscopy [82,86,92,[103][104][105] and low temperature laser-based high resolution spectroscopy such as matrix isolation [106][107][108][109], supersonic jet [107,[109][110][111], and Shpol'skii [107,109,112] and host matrix. The excited states of host matrix are usually band shape and dispersed (delocalized) over many molecules [113,114], where the excited states of the guest molecules are localized in much lower energy level and referred to as matrix isolated since they are decoupled from the host matrix.…”
Section: One-electron Oxidation and Metabolitesmentioning
confidence: 99%